2016
DOI: 10.1111/fog.12189
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Pacific North Equatorial Current and its implications on Japanese eel (Anguilla japonica) larval migration

Abstract: The zonal velocity produced by a Regional Ocean Modeling System (ROMS)‐based Pacific Ocean circulation model was validated against in situ measurements along the 137°E longitude. The Pacific model successfully reproduced the position and the shape of the North Equatorial Current (NEC) as well as the latitude of maximum surface velocity in the NEC region (8–17°N). The flow field produced by the Pacific model was then used to conduct numerical Lagrangian experiments, in which passive particles were released alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…Conversely, the abundance of conger showed a reduction in El Niño year in May 2015. These results implied that the climate variability (such as El Niño and La Niña) and the subsequent changes in the strength of currents and the abundance of nutrients were probably the critical factors that affected the larval transport of this long‐distance migratory fish, which was consistent with the similar studies for Japanese eel ( Anguilla japonica ), European eel ( Anguilla anguilla ), and American eel ( Anguilla rostrata ) (Egg, Mueller, Pander, Knott, & Geist, ; Han et al, ; Hsu, Xue, Chai, Xiu, & Han, ; Kim et al, ; Rypina, Kirincich, Lentz, & Sundermeyer, ; Wu, Wang, Lin, & Chao, ). However, most oceanic phenomena present decadal variations in both regional and global scales, which explains the insignificant influence of climate variability on the population dynamics of whitespotted conger owing to the limitation of time series length in this study (Han et al, ; Tuo et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, the abundance of conger showed a reduction in El Niño year in May 2015. These results implied that the climate variability (such as El Niño and La Niña) and the subsequent changes in the strength of currents and the abundance of nutrients were probably the critical factors that affected the larval transport of this long‐distance migratory fish, which was consistent with the similar studies for Japanese eel ( Anguilla japonica ), European eel ( Anguilla anguilla ), and American eel ( Anguilla rostrata ) (Egg, Mueller, Pander, Knott, & Geist, ; Han et al, ; Hsu, Xue, Chai, Xiu, & Han, ; Kim et al, ; Rypina, Kirincich, Lentz, & Sundermeyer, ; Wu, Wang, Lin, & Chao, ). However, most oceanic phenomena present decadal variations in both regional and global scales, which explains the insignificant influence of climate variability on the population dynamics of whitespotted conger owing to the limitation of time series length in this study (Han et al, ; Tuo et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Examination of the hydrographic data collected by the submersible and comparison to the hydrographic sections plotted from 5 X-CTD deployments crossing through the study area indicated that it was in a zone with very gradual temperature decreases with depth and minimal salinity changes (34.4 from ∼300-800 m) below the high-salinity layer of Subtropical Underwater (STUW), which is a typical feature of this area (see [53]) (Figure 4). The latitude of the observation was within the main part of the westward flow of the North Equatorial Current [54,55].…”
Section: Resultsmentioning
confidence: 99%
“…Overfishing and habitat loss due to human activities were considered to be one of the primary reasons causing the eel recruitment decline 7 . Changes in ocean circulation or oceanic conditions may also significantly affect eel recruitment 8 15 , or both types of factors have likely contributed 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The migration process of Japanese eels, however, is not well understood due to limited direct observational evidence on adult migration 23 or larval dispersal 24 . Numerical modelling methods, therefore, have been used to simulate the potential migration paths of Japanese eels, and to evaluate their linkages to ocean-atmosphere changes 12 , 14 , 15 , 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation